Composite microspheres for copper CMP with mesoporous core-shell structure and preparation method thereof, chemical mechanical polishing liquid and application thereof

The mesoporous SiO2 core was prepared by the template method and the SiO2/CeO2 composite microspheres with a cerium source formed into a core-shell structure were introduced, which solved the problem of high surface roughness of copper substrate polishing, and achieved improvement of surface defects and improvement of polishing rate.

CN116144323BActive Publication Date: 2025-02-28GUANGDONG ARTES NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211613769.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2025-02-28
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the surface roughness of copper substrate polishing, improve surface defects, and increase polishing rate.

Method used

The mesoporous SiO2 core was prepared by the template method, and then the cerium source was introduced to prepare SiO2/CeO2 composite microspheres with core-shell-covered structures, and a corresponding chemical mechanical polishing liquid was prepared for copper chemical mechanical polishing.

Benefits of technology

By using SiO2/CeO2 composite microspheres with mesoporous core-shell structures, the surface roughness of copper substrate polishing is significantly reduced, surface defects are improved, and polishing rate is increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004001247610000101
    Figure BDA0004001247610000101
  • Figure BDA0004001247610000102
    Figure BDA0004001247610000102
  • Figure HDA0004001247620000011
    Figure HDA0004001247620000011
Patent Text Reader

Abstract

The present invention relates to a composite microsphere for copper CMP with a mesoporous core-shell structure, a preparation method thereof, a chemical mechanical polishing liquid and an application thereof. The composite microsphere has mesoporous SiO2 as a core and CeO2 as a shell. During preparation, a template agent and a silicon source are first used to prepare mesoporous SiO2 microspheres by a template method as the core of the core-shell structure; then a cerium source and a precipitant are used to disperse and synthesize SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure. The chemical mechanical polishing liquid comprises SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure, a corrosion inhibitor, an oxidant and a complexing agent. The polishing liquid is applied to copper chemical mechanical polishing. Compared with the prior art, the composite microspheres prepared by the present invention have uniform surface coating, good monodispersity, simple preparation process, and can be used in the fields of copper sheet chemical mechanical polishing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nano material preparation, and more specifically to the field of preparation technology of polishing abrasive grains for copper surface precision polishing, and specifically to a composite microsphere for copper CMP with a mesoporous core-shell structure and a preparation method thereof, a chemical mechanical polishing liquid and an application thereof. Background Art

[0002] With the rapid development of integrated circuits (ICs), copper, which has electrical properties such as low resistivity and high electron mobility resistance, has gradually replaced aluminum and become the wiring layer metal of very large scale integrated circuits (VLSI). As a result, achieving global planarization of copper has become a new challenge in the development of integrated circuits. Chemical mechanical polishing (CMP) is currently the only method that can achieve global planarization at the same time. Abrasive is one of the important parameters of CMP and has a significant impact on polishing quality and polishing efficiency.

[0003] The polishing abrasives reported so far include SiO2, Al2O3, CeO2, Fe3O4, etc., while there are fewer reports on abrasives for copper substrates (such as CN 105800664 A). Since a single abrasive can no longer meet the increasing demand for ultra-precision surface polishing. Therefore, abrasives with composite properties based on a core-shell structure are the key to improving the polishing effect. The core-shell structure with SiO2 as the core and CeO2 as the shell has the characteristics of high biocompatibility, high stability, high polishing efficiency, etc., and has significant advantages over a single abrasive. At present, the application of this abrasive is mainly concentrated in the aspects of dispersibility and adsorption of nano-composite abrasive particles. Although it has been applied in the field of CMP (such as CN 107129762A, CN 106987229A), it is rarely used in copper substrates. Summary of the invention

[0004] The purpose of the present invention is to overcome at least one of the defects of the above-mentioned prior art and to provide a composite microsphere for copper CMP with a mesoporous core-shell structure, which can effectively reduce the surface roughness of the copper substrate polishing, improve surface defects, and help to increase the polishing rate, and a preparation method thereof, a chemical mechanical polishing liquid and its application.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] The invention discloses a SiO2 / CeO2 composite microsphere for copper CMP with a mesoporous core-shell structure. The composite microsphere has mesoporous SiO2 as a core and CeO2 as a shell.

[0007] A method for preparing SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure as described above, wherein the method first uses a template agent and a silicon source to prepare mesoporous SiO2 microspheres as the inner core of the core-shell structure by a template method; and then uses a cerium source and a precipitant to disperse and synthesize SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure.

[0008] Further, the method comprises the following steps:

[0009] Dispersing the template in a solvent, adding a precipitant dropwise to obtain a solution A, stirring the solution A, and adding a silicon source to obtain a solution B;

[0010] After centrifugation of solution B, mesoporous SiO2 microspheres were obtained after washing, drying and calcination;

[0011] Dispersing mesoporous SiO2 microspheres in a solvent, and obtaining a solution C after ultrasonication and / or stirring;

[0012] The cerium source and the precipitant are dispersed in a solvent, and solution D is obtained after ultrasonication and / or stirring. Solution D is added to solution C, and solution E is obtained after stirring and reaction.

[0013] Solution E is centrifuged, washed, dried, calcined, ground and sieved to obtain SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure.

[0014] Furthermore, the usage ratio of the template agent, the precipitant and the silicon source is (0.4-0.8) g: (1-2) ml: (1-3) ml;

[0015] The mass ratio of the mesoporous SiO2 microspheres, the cerium source and the precipitant is (0.4-1):(0.6-1.2):(0.96-1.92);

[0016] The template comprises hexadecyltrimethylammonium bromide (CTAB), the precipitant comprises ammonia water (NH3·H2O) or hexamethylenetetramine (HMT), the silicon source comprises tetraethyl orthosilicate (TEOS), the cerium source comprises cerium nitrate hexahydrate [Ce(NO3)3·6H2O], and the solvent comprises water and / or alcohol;

[0017] The stirring speed is 300-800r / min, and the time is 2-6h; the centrifugal speed is 8000-10000r / min, and the time is 5-10min;

[0018] The drying temperature is 55-65°C, the time is 12-24h, the calcination temperature is 450-650°C, and the holding time is 2-4h;

[0019] The ultrasonic treatment time is 10-15 minutes, and the washing is carried out using alcohol and water respectively.

[0020] Furthermore, the precipitant in solution A is ammonia water (NH3·H2O), the precipitant in solution D is hexamethylenetetramine (HMT), the solvent in solution A is a mixture of water and alcohol, the solvent in solution C is alcohol, and the solvent in solution C is water; the ammonia water is commercially available 25-28wt% concentrated ammonia water.

[0021] The stirring rate of solution A is 350-800 r / min, the time is 2-4 h, and the temperature is room temperature; the stirring rate of solution E is 300-600 r / min, the time is 3-6 h, and the temperature is 60-75°C;

[0022] The washing times are no less than 3 times, and the alcohol includes ethanol.

[0023] Furthermore, the volume ratio of water to alcohol in solution A is (150-200):(40-60).

[0024] A chemical mechanical polishing liquid comprises the SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure as described above, a corrosion inhibitor, an oxidant and a complexing agent.

[0025] Furthermore, in the polishing liquid, the mass content of the composite microspheres is 0.5-10%, the mass content of the corrosion inhibitor is 0.001-0.5%, the mass content of the oxidant is 0.5-5%, the mass content of the complexing agent is 0.05-5%, and the balance is the solvent;

[0026] The corrosion inhibitor includes nitrogen azole compounds, the oxidant includes strong acid compounds, the complexing agent includes aminocarboxylic acid compounds, and the solvent includes water.

[0027] Furthermore, in the polishing liquid, the mass content of the composite microspheres is 1-5%, the mass content of the corrosion inhibitor is 0.01-0.05%, the mass content of the oxidant is 0.5-2%, and the mass content of the complexing agent is 0.5-1%;

[0028] The azole compounds include benzotriazole, 5-methylbenzotriazole, 5-carboxybenzotriazole, 1-hydroxybenzotriazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, 5-methyltetrazolyl, 5-phenyl-1,2,4-triazole or 1-hydroxybenzotriazole;

[0029] The strong acid compounds include peroxide compounds such as hydrogen peroxide, performic acid, persulfate, percarbonate, and periodic acid, perchloric acid, perboric acid or potassium permanganate;

[0030] The aminocarboxylic acid compound includes glycine, alanine, valine, leucine, proline, phenylalanine, tyrosine, tryptophan, lysine, arginine, histidine, serine, aspartic acid, threonine, glutamic acid, asparagine, glutamine, nitrilotriacetic acid, ethylenediaminetetraacetic acid or cyclohexanediaminetetraacetic acid.

[0031] An application of the chemical mechanical polishing liquid as described above, the polishing liquid is used for copper chemical mechanical polishing, the pH of the chemical mechanical polishing liquid is adjusted to 8-8.5 during polishing, and the polishing process conditions include: polishing pressure of 1-3.4psi, sample loading plate speed of 60-90r / min, polishing plate speed of 90-120r / min, polishing liquid feed flow rate of 60-120ml / min, and polishing time of 1-5min.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The present invention adopts a template method to prepare a mesoporous SiO2 core, and then introduces a cerium source to prepare a SiO2 / CeO2 composite microsphere with a core-shell coating structure. The material has a mesoporous structure, and a low elastic modulus can reduce mechanical damage caused by polishing.

[0034] (2) The present invention has low production cost, simple preparation process, strong experimental repeatability, and has application value in improving the polishing effect of copper substrates;

[0035] (3) The composite microspheres prepared by the present invention have uniform surface coating and good monodispersity, and the preparation process is simple, and can be used in the field of chemical mechanical polishing of copper sheets. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope image of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1;

[0037] Figure 2 This is a nitrogen adsorption curve of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1;

[0038] Figure 3 The pore size distribution curve of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1;

[0039] Figure 4 This is an atomic force microscope two-dimensional morphology image of the surface of the copper sheet after polishing of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1;

[0040] Figure 5 This is an atomic force microscope three-dimensional morphology image of the surface of the copper sheet after polishing of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Unless otherwise specified, % herein are all mass %.

[0042] A method for preparing SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure, using hexadecyltrimethylammonium bromide (CTAB) as a template agent and tetraethyl orthosilicate (TEOS) as a silicon source, preparing mesoporous SiO2 microspheres as the core of the core-shell structure by a template method; then using hexahydrated cerium nitrate Ce(NO3)3·6H2O as a cerium source, hexamethylenetetramine (HMT) and ammonia water (NH3·H2O) as precipitants, dispersed synthesis in an ethanol-deionized water system. After the solution is centrifuged and washed with deionized water and ethanol to obtain a centrifuged product, the core-shell structure can be obtained by vacuum drying and calcining, comprising the following steps:

[0043] Step 1: Take CTAB, disperse it in a mixed solution of deionized water and ethanol, add ammonia water dropwise to obtain solution A, stir solution A with constant temperature magnetic force, and add TEOS dropwise to obtain solution B; the amount of CTAB added is 0.4-0.8g, the amount of NH3·H2O added is 1-2ml, and the amount of TEOS added is 1-3ml. The temperature is 25°C, the magnetic stirring rate is 350-800r / min, and the reaction time is 2-4h.

[0044] Step 2: After centrifuging solution B, wash it with ethanol and deionized water respectively, vacuum dry it, and calcine it to remove the template to obtain mesoporous SiO2 microspheres; the centrifugal speed of solution B is 10,000 rpm for 5 minutes; the washing method is to wash it with ethanol and deionized water respectively for 3 times, the centrifugal speed is 8,000 rpm for 5 minutes. The vacuum drying temperature is 60°C, the drying time is 12-24h, the calcination temperature is 450-650°C, and the insulation time is 2-4h.

[0045] Step three, take mesoporous SiO2 microspheres, disperse them in ethanol, and perform ultrasonic treatment to obtain solution C, and subject solution C to constant temperature magnetic stirring; the amount of mesoporous SiO2 microspheres added is 0.4-1g, and solution C is subjected to ultrasonic treatment for 10-15 minutes.

[0046] Step 4: Disperse Ce(NO3)3·6H2O and HMT in deionized water, perform ultrasonic treatment, obtain solution D, add dropwise to solution C, obtain solution E, and perform constant temperature magnetic stirring reaction on solution E; the amount of Ce(NO3)3·6H2O added is 0.6-1.2g, the amount of HMT added is 0.96-1.92g, and solution D is ultrasonically treated for 10-15 minutes. The temperature is 60-75°C, the magnetic stirring rate is 300-600r / min, and the reaction time is 3-6h.

[0047] Step 5: After centrifuging solution E, wash it with deionized water and ethanol, vacuum dry it, calcine it, grind and sieve it, and obtain nano-scale mesoporous SiO2 / CeO2 composite microspheres with a core-shell structure. Solution E is centrifuged at a speed of 10,000 rpm for 10 minutes; the washing method is to wash it with ethanol and deionized water three times, respectively, at a centrifugal speed of 8,000 rpm for 5 minutes. The vacuum drying temperature is 60°C, the drying time is 12-24h, the calcination temperature is 450-650°C, and the insulation time is 2-4h.

[0048] A chemical mechanical polishing liquid, the components of which include SiO2 / CeO2 composite microspheres with a core-shell structure having mesopores, a corrosion inhibitor, an oxidant and a complexing agent. The content of the SiO2 / CeO2 composite microspheres is 0.5-10%. The corrosion inhibitor is benzotriazole, 5-methylbenzotriazole, 5-carboxybenzotriazole, 1-hydroxybenzotriazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, 5-methyltetrazole, 5-phenyl-1,2,4-triazole, 1-hydroxybenzotriazole and other nitrogen azole compounds. The content of the corrosion inhibitor is 0.001-0.5%. The oxidant is a peroxide compound such as hydrogen peroxide, performic acid, persulfate, percarbonate and other peroxide compounds and a strong acid compound such as periodic acid, perchloric acid, perboric acid, potassium permanganate and the like. The content of the oxidant is 0.5-5%. The complexing agent is aminocarboxylic acid compounds such as glycine, alanine, valine, leucine, proline, phenylalanine, tyrosine, tryptophan, lysine, arginine, histidine, serine, aspartic acid, threonine, glutamic acid, asparagine, glutamine, nitrilotriacetic acid, ethylenediaminetetraacetic acid, and cyclohexanediaminetetraacetic acid. The content of the complexing agent is 0.05-5%.

[0049] A method for preparing SiO2 / CeO2 composite microspheres with a mesoporous core-shell structure for copper CMP is used in copper chemical mechanical polishing. The prepared SiO2 / CeO2 composite microspheres with a mesoporous core-shell structure are prepared into a polishing liquid, and a polishing test is carried out by an automatic precision grinding and polishing machine.

[0050] The preparation process of the polishing liquid includes: dispersing the composite microspheres in deionized water to form a uniform emulsion, adding a corrosion inhibitor, an oxidant, and a complexing agent, and then adjusting the pH to 8-8.5 with sodium hydroxide (NaOH), and uniformly stirring the polishing liquid by ultrasonic magnetic force. The process conditions of polishing include: polishing pressure of 1-3.4psi, sample plate speed of 60-90r / min, polishing plate speed of 90-120r / min, polishing liquid feed flow rate of 60-120ml / min, and polishing time of 1-5min.

[0051] Compared with CN106987229A, the abrasive prepared by the invention is used for silicon wafer polishing, and the components and proportions added in the polishing liquid are different, while the copper substrate polishing liquid has more components, and the effects are different. For different polishing substrates, although the polishing methods are roughly similar, the emphasis is different. The chemical mechanical polishing of copper wafers focuses on the polishing liquid first forming a chemical reaction on the copper surface to generate a passivation film and a composite layer film, and then mechanically removing it through the abrasive.

[0052] Copper substrates are softer and have a lower elastic modulus than silicon wafers, silicon carbide, sapphire, glass and other substrates (105GPa for copper at 20°C vs 190GPa for silicon at 20°C). The choice of abrasives is more particular. The composite abrasive shell layer coated with cerium oxide (softer than the core layer silicon oxide) used in this application can reduce the mechanical scratches caused by the abrasive on the copper surface. The support provided by the core layer can effectively remove the chemical reaction layer.

[0053] Example 1

[0054] A composite microsphere for copper CMP with a mesoporous core-shell structure and a preparation method thereof, a chemical mechanical polishing liquid and an application thereof, the specific operation is as follows:

[0055] Step 1: Take 0.42 g of CTAB and disperse it in a flask containing a mixed solution of 160 ml of deionized water and 50 ml of anhydrous ethanol, add 2 ml of ammonia water to obtain solution A, place it in an oil bath set at 25°C, stir it at a magnetic stirring rate of 350 r / min for 30 min, then add a mixed solution of 2.5 ml of TEOS dissolved in 40 ml of anhydrous ethanol dropwise to obtain solution B, and continue stirring for 2 h;

[0056] Step 2: After the reaction is completed, the obtained solution is centrifuged, washed with deionized water and ethanol three times respectively, transferred to a vacuum drying oven for drying for 12 hours, placed in a tubular furnace at a temperature of 550°C to calcine and remove the template, and kept warm for 3 hours. After naturally cooling to room temperature, it is taken out to obtain mesoporous SiO2 microspheres.

[0057] Step 3, taking 0.62 g of mesoporous SiO2 microspheres, dispersing them in a flask containing 60 ml of ethanol, and subjecting them to ultrasonic treatment for 10 min to obtain solution C;

[0058] Step 4: Disperse 1.06 g Ce(NO3)3·6H2O and 1.42 g HMT in a beaker containing 100 ml deionized water, and perform ultrasonic treatment for 15 min to obtain solution D, which is then added dropwise to solution C through a separatory funnel to obtain solution E, which is placed in an oil bath set at 75°C and stirred at a magnetic stirring rate of 600 r / min for 4 h;

[0059] Step 5. After the reaction is completed, the resulting solution is centrifuged, washed three times with deionized water and ethanol respectively, dried in a vacuum drying oven for 24 hours, calcined in a tubular furnace at 550°C for 3 hours, and ground and sieved to obtain light yellow mesoporous SiO2 / CeO2 composite microspheres with a core-shell structure.

[0060] Figure 1 This is a transmission electron microscope image of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1. It can be seen that the prepared mesoporous SiO2 / CeO2 particles are regular spherical, and it can be clearly seen that the shell of the composite microspheres is evenly covered with a layer of CeO2, which has a typical core-shell coating structure. The particle size analysis test was performed using Nano-Measurer software, and the average particle size of the prepared core was about 275nm, and the particle size of the shell was about 21nm.

[0061] Figure 2 and Figure 3 The nitrogen adsorption curve and pore size distribution curve of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1. It can be seen that the nitrogen adsorption curve of the prepared mesoporous SiO2 / CeO2 particles conforms to the type IV isotherm. Through calculation and analysis, the specific surface area is about 919.53 m 2 / g, the pore size distribution is narrow, and the average pore size is about 2.87nm.

[0062] The composite microspheres prepared by the process parameters of Example 1 were dispersed in deionized water to form an emulsion with a mass concentration of 2%, and then 0.01% of benzotriazole was added as a corrosion inhibitor, 1% of hydrogen peroxide was added as an oxidant, and 0.5% of glycine was added as a complexing agent. The pH was then adjusted to 8.5 with NaOH, and the polishing liquid was obtained after ultrasonic magnetic stirring.

[0063] Under the following polishing process conditions: polishing pressure of 3 psi, sample plate speed of 75 r / min, polishing plate speed of 90 r / min, polishing liquid feed flow of 90 ml / min, polishing time of 3 min, the copper sheet was polished by an automatic precision grinding and polishing machine.

[0064] Figure 4 and Figure 5The two-dimensional and three-dimensional atomic force microscope morphology images of the surface of the copper sheet after polishing of the mesoporous SiO2 / CeO2 composite microspheres prepared in Example 1. The polished surface was analyzed by NanoScope Analysis software, and the average surface roughness of the copper sheet after polishing was about 0.496nm; the mass loss of the copper sheet before and after polishing was calculated, and the polishing rate obtained by the material removal formula was 223nm / min.

[0065] In CN106987229A, the polishing liquid prepared contains: mesoporous silicon oxide / cerium oxide composite particles (SiO2 / CeO2), deionized water (DIW), sodium dodecylbenzene sulfonate (SDBS), sodium hydroxide (NaOH), which are respectively abrasive, solvent, dispersant, and pH regulator. It acts on the silicon wafer substrate, focusing on mechanical removal. SDBS allows the abrasive to be better dispersed in the polishing liquid, and pH adjusts the acidity to prevent corrosion caused by acidity. The abrasive and the silicon substrate will form a Si-Ce-Si combination, and then mechanical removal is performed by the abrasive. This polishing liquid cannot be applied to copper substrates because there is no component that can react with the surface of the copper substrate for chemical mechanical polishing.

[0066] The polishing liquid of the present application takes Example 1 as an example, and its components are as follows: mesoporous silicon oxide / cerium oxide composite particles (SiO2 / CeO2), deionized water (DIW), hydrogen peroxide (H2O2), benzotriazole (BTA), glycine (GLY), sodium hydroxide (NaOH), which are respectively abrasive, solvent, oxidant, corrosion inhibitor, complexing agent, and pH adjuster. Among them, the copper substrate first needs to react with the hydrogen peroxide in the polishing liquid to form a film, and then the OH group dissociates the Cu 2+ ions, an oxide layer will be formed first; GLY and BTA will be further 2+ The ions combine to form chelates and complexes, which become composite layers. Finally, the surface composite layer is mechanically removed by abrasive particles to form a new copper layer without disc pits. Although both are CMP, the added components are different and the action mechanism is different. The polishing liquid of CN106987229A and the polishing liquid of this application cannot be used interchangeably.

[0067] Example 2

[0068] The steps of this embodiment are basically the same as those of the above-mentioned embodiment 1, except that: in step 1, the amount of CTAB added is 0.78 g, the magnetic stirring rate is 600 r / min, and the amount of TEOS added is 2 ml; in step 2, the temperature of the tube furnace is set to 650°C, and it is kept warm for 2 hours; in step 3, the amount of mesoporous SiO2 microspheres added is 1.02 g; in step 4, the amount of Ce(NO3)3·6H2O added is 1.58 g, the amount of HMT added is 1.92 g, the oil bath temperature is 65°C, and the magnetic stirring rate is 450 r / min; in step 5, the temperature of the tube furnace is set to 650°C, and it is kept warm for 2 hours.

[0069] The composite microspheres prepared by the process parameters of Example 2 were dispersed in deionized water to prepare an emulsion with a mass concentration of 1%, and then 0.05% of 1,2,4-triazole was added as a corrosion inhibitor, 1% of hydrogen peroxide was added as an oxidant, and 0.5% of glycine was added as a complexing agent. Then, the pH was adjusted to 8.0 with sodium hydroxide, and the polishing liquid was obtained after being uniformly stirred;

[0070] Under the following polishing process conditions: polishing pressure of 3 psi, sample plate speed of 87 r / min, polishing plate speed of 93 r / min, polishing liquid feed flow of 90 ml / min, polishing time of 5 min, the copper sheet was polished by an automatic precision grinding and polishing machine.

[0071] Example 3

[0072] The steps of this embodiment are basically the same as those of the above-mentioned embodiment 1, except that: in step 1, the amount of CTAB added is 0.41 g, the magnetic stirring rate is 400 r / min, and the amount of TEOS added is 1 ml; in step 2, the temperature of the tube furnace is set to 550°C and kept warm for 4 hours; in step 3, the amount of mesoporous SiO2 microspheres added is 0.42 g; in step 4, the amount of Ce(NO3)3·6H2O added is 0.66 g, the amount of HMT added is 0.99 g, the oil bath temperature is 70°C, and the magnetic stirring rate is 450 r / min; in step 5, the temperature of the tube furnace is set to 550°C and kept warm for 4 hours.

[0073] The composite microspheres prepared by the process parameters of Example 3 were dispersed in deionized water to prepare an emulsion with a mass concentration of 3%, and then 0.02% of benzotriazole was added as a corrosion inhibitor, 1% of H2O2 was added as an oxidant, and 1% of valine was added as a complexing agent. Then, the pH was adjusted to 8.0 with sodium hydroxide, and the polishing liquid was obtained after stirring evenly.

[0074] Under the following polishing process conditions: polishing pressure of 1 psi, sample plate speed of 60 r / min, polishing plate speed of 90 r / min, polishing liquid feed flow of 80 ml / min, polishing time of 3 min, the copper sheet was polished by an automatic precision grinding and polishing machine.

[0075] Example 4

[0076] The steps of this embodiment are basically the same as those of the above-mentioned embodiment 1, except that: in step 1, the amount of CTAB added is 0.50 g, the magnetic stirring rate is 750 r / min, and the amount of TEOS added is 3 ml; in step 2, the temperature of the tube furnace is set to 500°C and kept warm for 3 hours; in step 3, the amount of mesoporous SiO2 microspheres added is 0.80 g; in step 4, the amount of Ce(NO3)3·6H2O added is 1.21 g, the amount of HMT added is 1.80 g, the oil bath temperature is 70°C, and the magnetic stirring rate is 550 r / min; in step 5, the temperature of the tube furnace is set to 500°C and kept warm for 3 hours.

[0077] The composite microspheres prepared by the process parameters of Example 4 were dispersed in deionized water to prepare an emulsion with a mass concentration of 5%, and then 0.01% of benzotriazole was added as a corrosion inhibitor, 1% of H2O2 was added as an oxidant, and 0.5% of glycine was added as a complexing agent. Then, the pH was adjusted to 8.5 with sodium hydroxide, and the polishing liquid was obtained after stirring evenly.

[0078] Under the following polishing process conditions: polishing pressure of 1 psi, sample plate speed of 90 r / min, polishing plate speed of 105 r / min, polishing liquid feed flow of 100 ml / min, polishing time of 3 min, the copper sheet was polished by an automatic precision grinding and polishing machine.

[0079] Table 1 shows the average surface roughness and polishing rate of the mesoporous SiO2 / CeO2 composite microspheres prepared in Examples 1-4 after being configured into a polishing liquid for CMP polishing of a copper substrate. Table 2 shows the polishing conditions of a conventional example formed by changing the components based on Example 1.

[0080] Table 1

[0081]

[0082] Table 2

[0083]

[0084] In Table 1-2, the pH only needs to be controlled within the alkaline range of 8-8.5, and there is no consideration of its acidity and alkalinity.

[0085] First of all, the types of ingredients in the polishing liquid. The current preparation trend is to develop in the direction of fewer types and lower concentrations. The abrasive concentration usually ranges from 1-40%. However, through literature review and continuous improvement of the polishing liquid, this application uses the smallest possible concentration ratio to achieve precision polishing; the oxidant is usually the second most added component, but a ratio higher than 5% will have great side effects on the polishing liquid, such as corroding the substrate and failing to effectively promote the forward reaction. It is usually controlled to be less than the abrasive concentration and greater than the addition amount of other ingredients; complexing agents and corrosion inhibitors are usually the third type of type, and they play a complexing role in the polishing liquid.

[0086] Because there are many influencing factors, the polishing rate and polishing effect brought by the type and dosage are still under continuous exploration. At the same time, how to achieve a balance between the polishing rate and the polishing effect has always been a research difficulty and is not a conventional choice. For example, Examples 1 and 4 are about the effect of different abrasive concentration changes on polishing. The increase in concentration will gradually increase the speed of mechanical removal and thus increase the polishing efficiency, but the surface roughness is not reduced, but improved. Examples 2 and 3 discuss the effects of different corrosion inhibitors and complexing agents on copper CMP. It should be noted here that benzotriazole and 1,2,4-triazole, glycine and valine are all the same type of compounds.

[0087] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A copper sheet chemical mechanical polishing liquid, characterized in that: The polishing liquid comprises SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure, a corrosion inhibitor, an oxidant and a complexing agent; In the polishing liquid, the mass content of the composite microspheres is 1-5%, the mass content of the corrosion inhibitor is 0.01-0.05%, the mass content of the oxidant is 0.5-2%, and the mass content of the complexing agent is 0.5-1%; The composite microspheres have mesoporous SiO2 as core and CeO2 as shell; The corrosion inhibitor includes azole compounds, and the azole compounds include benzotriazole, 5-methylbenzotriazole, 5-carboxybenzotriazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, 5-methyltetrazolyl, 5-phenyl-1,2,4-triazole or 1-hydroxybenzotriazole; The oxidant includes a strong acid compound, and the strong acid compound includes hydrogen peroxide, performic acid, persulfate, percarbonate, periodic acid, perchloric acid, perboric acid or potassium permanganate; The complexing agent includes an aminocarboxylic acid compound, and the aminocarboxylic acid compound includes glycine, alanine, valine, leucine, proline, phenylalanine, tyrosine, tryptophan, lysine, arginine, histidine, serine, aspartic acid, threonine, glutamic acid, asparagine, glutamine, nitrilotriacetic acid, ethylenediaminetetraacetic acid or cyclohexanediaminetetraacetic acid; The preparation method of SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure comprises the following steps: (S1) dispersing the template in a solvent, adding a precipitant dropwise to obtain a solution A, stirring the solution A, and adding a silicon source to obtain a solution B. Wherein, the usage ratio of the template agent, the precipitant and the silicon source is (0.4-0.8) g: (1-2) mL: (1-3) mL; The template agent includes hexadecyltrimethylammonium bromide, the solvent is a mixture of water and alcohol, and the volume ratio of water to alcohol is (150-200): (40-60); the precipitant is ammonia water, and the silicon source includes tetraethyl orthosilicate; The stirring rate is 350-800 r / min, the time is 2-4 h, and the temperature is room temperature; (S2) After centrifuging solution B, washing, drying and calcining are performed to obtain mesoporous SiO2 microspheres; Wherein, the centrifugal speed is 8000-10000 r / min, and the time is 5-10 min; The washing adopts alcohol and water respectively; The drying temperature is 55-65°C, the time is 12-24 h, the calcination temperature is 450-650°C, and the holding time is 2-4 h; (S3) dispersing mesoporous SiO2 microspheres in a solvent, and obtaining solution C after ultrasonication and / or stirring, dispersing a cerium source and a precipitant in a solvent, and obtaining solution D after ultrasonication and / or stirring, and adding solution D to solution C, and obtaining solution E after stirring for reaction; the mass ratio of the mesoporous SiO2 microspheres, the cerium source and the precipitant is (0.4-1): (0.6-1.2): (0.96-1.92); Wherein, the solvent in solution C is alcohol, the solvent in solution D is water, the precipitant is hexamethylenetetramine, and the cerium source includes cerium nitrate hexahydrate; The ultrasonic treatment time is 10-15 min. The stirring rate in solution E is 300-600 r / min, the time is 3-6 h, and the temperature is 60-75°C; (S4) After centrifuging the solution E, washing, drying, calcining, grinding and sieving, SiO2 / CeO2 composite microspheres for copper CMP with a mesoporous core-shell structure are obtained; The number of washings is not less than 3 times.

2. An application of the copper sheet chemical mechanical polishing liquid as claimed in claim 1, characterized in that: The polishing liquid is used for copper chemical mechanical polishing. During polishing, the pH value of the chemical mechanical polishing liquid is adjusted to 8-8.

5. The polishing process conditions include: polishing pressure of 1-3.4 psi, sample plate rotation speed of 60-90 r / min, polishing plate rotation speed of 90-120 r / min, polishing liquid feed flow rate of 60-120 mL / min, and polishing time of 1-5 min.

Citation Information

Patent Citations

  • Method for preparing ceria abrasive and application thereof in CMP (Chemical Mechanical Polishing)

    CN105800664A

  • Polishing solution for polishing silicon carbide chemical machinery and preparation method of polishing solution

    CN107129762A

  • Core-shell cladding structure composite particle, preparation method and uses thereof

    CN106987229A

  • Cmp slurry composition for polishing copper line and polishing method using same

    CN107109135A